2018
DOI: 10.3748/wjg.v24.i43.4835
|View full text |Cite
|
Sign up to set email alerts
|

Promoting genetics in non-alcoholic fatty liver disease: Combined risk score through polymorphisms and clinical variables

Abstract: Non-alcoholic fatty liver disease (NAFLD) has a prevalence of approximately 30% in western countries, and is emerging as the first cause of liver cirrhosis and hepatocellular carcinoma (HCC). Therefore, risk stratification emerges as fundamental in order to optimize human and economic resources, and genetics displays intrinsic characteristics suitable to fulfill this task. According to the available data, heritability estimates for hepatic fat content range from 20% to 70%, and an almost 80% of shared heritabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 55 publications
0
35
0
1
Order By: Relevance
“…(43) Routine NAFLD screening is not currently recommended by the American Association for the Study of Liver Diseases because of limitations of diagnostic tests and treatment options. (44) Because of strong NAFLD heritability, ranging from 20% to 70% depending on study characteristics, genetic polymorphisms may be useful for risk stratification. (45) Adding I148M data to patient charts for liver health surveillance should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(43) Routine NAFLD screening is not currently recommended by the American Association for the Study of Liver Diseases because of limitations of diagnostic tests and treatment options. (44) Because of strong NAFLD heritability, ranging from 20% to 70% depending on study characteristics, genetic polymorphisms may be useful for risk stratification. (45) Adding I148M data to patient charts for liver health surveillance should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A "NAFLD" diagnosis requires exclusion of significant alcohol use (>21 drinks, on average, per week for men or >14 drinks, on average, per week for women). (44) Given that almost 40% of U.S. adults are now obese, mixed forms of NAFLD and alcoholic FLD are increasingly likely. (47,48) In addition, alcohol intake may interact with genetic variants that predispose to liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…(3) data collection and analysis methods unscientific or inappropriate; (4) lack of detailed genotyping data; (5) no-case-control study; (6) in animal studies.…”
Section: Inclusion and Exclusion Criteria Of The Literaturementioning
confidence: 99%
“…A single nucleotide polymorphism (SNP) is a result of transition or transversion mutation of a single base, and is significantly associated with various genetic diseases [4]. Moreover, current studies have initially demonstrated that different SNPs have different roles in liver damage, and some of them increase the risk of chronic liver disease and HCC through genetic variation alone or in combination with clinical variables [5]. The role of a common non-synonymous polymorphism in transmembrane 6 superfamily member 2 (rs58542926 c.449 C > T, p.Glu167Lys, E167K) in lipid metabolism and chronic liver disease has attracted attention, with multiple studies focused on the role of TM6SF2 rs58542926 variant in chronic liver disease and HCC [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although lifestyle variations in those groups have to be considered, underlying genetic factors could further account for the skewed prevalence of NAFLD. Further supporting a genetic substrate, NAFLD heritability increases by up to 27% in families with certain gene variants 3 . Similarly, sex differences in NAFLD epidemiology and clinical features have been reported.…”
Section: Introductionmentioning
confidence: 81%